Use of programmable versus nonprogrammable shunts in the management of normal pressure hydrocephalus: A multicenter retrospective study with cost–benefit analysis in Turkey. Issue 39 (September 2017) - Serarslan, Yurdal; Yilmaz, Atilla; Çakır, Mürteza; Güzel, Ebru; Akakin, Akin; Güzel, Aslan; Urfalı, Boran; Aras, Mustafa; Kaya, Mustafa Emrah; Yılmaz, Nebi
Abstract : Abstract: Ventriculoperitoneal shunt systems that are used in the treatment of normal pressure hydrocephalus are often associated with drainage problems. Adjustable shunt systems can prevent or treat these problems, but they may be expensive. The aim of our study is to compare the complications and total cost of several shunt systems. Patients with normal pressure hydrocephalus who underwent ventriculoperitoneal shunting between 2011 and 2016 were included in the study. The study involves patient consent and the informed consent was given. Complications and the average cost per person were compared between patients with adjustable and nonadjustable shunts. Shunt prices, surgical complications, and revision costs were taken into account to calculate the average cost. Of the 110 patients who were evaluated, 80 had a nonadjustable shunt and 30 had an adjustable shunt. In the group with adjustable shunts, the rates of subdural effusion and hematoma were 19.73% and 3.29%, respectively. In the group with nonadjustable shunts, these rates were 22.75% and 13.75%, respectively. One patient in the adjustable group underwent surgery for subdural hematoma, while 8 patients in the nonadjustable group underwent the same surgery. Ten patients required surgical intervention for subdural effusion and existing shunt systems in these patients were replaced by an adjustable shunt system. When these additional costs were factored into the analysis, the difference in cost between the shunt systems was reduced from 600 United States dollars (USD) to 111 USD. When the complications and additional costs that arise during surgical treatment of normal pressure hydrocephalus were considered, the price difference between adjustable and nonadjustable shunt systems was estimated to be much lower.